A facile approach for the synthesis of Z-scheme photocatalyst ZIF-8/g-C3N4 with highly enhanced photocatalytic activity under simulated sunlight. (27th June 2018) - Liu, Xiang; Zhang, Jing; Dong, Yuming; Li, Hexing; Xia, Yongmei; Wang, Haijun
Abstract : The enhanced photocatalytic activity of ZIF-8/g-C3 N4 composites can be attributed to strong interfacial interaction, which promoted the photo-generated electron–hole separation. Abstract : In this study, ZIF-8-modified g-C3 N4 (ZIF-8/g-C3 N4 ) composites were successfully synthesized by hydrothermal reaction. The properties of the ZIF-8/g-C3 N4 composites were analyzed by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), UV-vis diffuse reflectance spectroscopy (UV-vis DRS) and photoluminescence (PL) spectroscopy. The results indicated that the ZIF-8 grew on the surface of the g-C3 N4, forming closely contacted interfaces between the ZIF-8 and the g-C3 N4 component. The photocatalytic performance of the ZIF-8/g-C3 N4 composites was evaluated through the photodegradation of Rhodamine B (RhB). The results showed that 99.8% of RhB was degraded by the ZIF-8/g-C3 N4 composite with 3 wt% of ZIF-8 in 60 min under simulated sunlight, which was much higher than that of pure g-C3 N4 and ZIF-8. This highly enhanced photocatalytic activity of the ZIF-8/g-C3 N4 composites can be mainly attributed to strong interfacial interaction promoting the photo-generated electron–hole separation and migration. The results of radical scavenger experiments showed that ˙O2 − and h + were the dominant reactive species in the photocatalytic reaction. In addition, the ZIF-8/g-C3 N4 composites showed excellent stability over several reaction cycles. Finally, a possible Z-scheme photocatalytic mechanism was proposed based on the experimental results.